ФОРМУВАННЯ ЗАГАЛЬНОЛЮДСЬКИХ ЦІННОСТЕЙ У СТАРШОКЛАСНИКІВ ЗАСОБАМИ УКРАЇНСЬКОЇ ЛІТЕРАТУРИ (Педагогіка вищої та середньої школи, 2007)
The article deals with some problems of value orientations in schoolboy life. The analysis of value orientations in pupl life in higher educational establishments of pedagogy is provided.